Functional Alterations in Cerebellar Functional Connectivity in Anxiety Disorders - Yoon Ji Lee; Xavier Guell; Nicholas A. Hubbard; Viviana Siless; Isabelle R. Frosch; Mathias Goncalves; Nicole Lo; Atira Nair; Satrajit S. Ghosh; Stefan G. Hofmann; Randy P. Auerbach; Diego A. Pizzagalli; et al. (The Cerebellum, 2021)
Adolescents with anxiety disorders exhibit excessive emotional and somatic arousal. Neuroimaging studies have shown abnormal cerebral cortical activation and connectivity in this patient population. The specific role of cerebellar output circuitry, specifically the dentate nuclei (DN), in adolescent anxiety disorders remains largely unexplored. Resting-state functional connectivity analyses have parcellated the DN, the major output nuclei of the cerebellum, into three functional territories (FTs) that include default-mode, salience-motor, and visual networks. The objective of this study was to understand whether FTs of the DN are implicated in adolescent anxiety disorders. Forty-one adolescents (mean age 15.19 ± 0.82, 26 females) with one or more anxiety disorders and 55 age- and gender-matched healthy controls completed resting-state fMRI scans and a self-report survey on anxiety symptoms. Seed-to-voxel functional connectivity analyses were performed using the FTs from DN parcellation. Brain connectivity metrics were then correlated with State-Trait Anxiety Inventory (STAI) measures within each group. Adolescents with an anxiety disorder showed significant hyperconnectivity between salience-motor DN FT and cerebral cortical salience-motor regions compared to controls. Salience-motor FT connectivity with cerebral cortical sensorimotor regions was significantly correlated with STAI-trait scores in HC ( R 2 = 0.41). Here, we report DN functional connectivity differences in adolescents diagnosed with anxiety, as well as in HC with variable degrees of anxiety traits. These observations highlight the relevance of DN as a potential clinical and sub-clinical marker of anxiety.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

A Theoretical Framework for the Evaluation of Massive Digital Participation Systems in Urban Planning - Mathias Hofmann; Sander Münster; Jörg Rainer Noennig (Journal of Geovisualization and Spatial Analysis, 2020)
Urban development that strives to meet democratic ideals and the needs of all stakeholders must incorporate public participation. Contemporary participation processes may employ digital tools that open new possibilities regarding the range of participants and the intensity of participation. In particular, they can uniquely allow for large and diverse groups of participants to be involved in collaborative design processes. Evaluating such processes is important because it allows for the justification of the necessary costs and efforts, as well as continuous improvement. Using the phases specified in the minimal viable process of the U_CODE project as an example, this paper aims at describing criteria for the evaluation of participation processes and propose several possible methods for their assessment. While the majority of these criteria resemble criteria traditionally used to assess public participation in general, this paper proposes an additional criterion, as well as ways of applying all of the criteria to digital participation methods. In addition, the criteria and methods described in this paper not only may be used for evaluative purposes during or after a digital participation process but may also be useful guidelines during the planning stages of participation processes. Hence, it may help to consider these criteria to assess the value of the process during its inception stage to avoid mistakes and to enhance the democratic value of the participation process.

Contrasting strategies for tree species to cope with heat and dry conditions at urban sites - Sten Gillner; Sandra Korn; Mathias Hofmann; Andreas Roloff (Urban Ecosystems, 2017)

Predicting tree preferences from visible tree characteristics - Mathias Hofmann; Tina Gerstenberg; Sten Gillner (European Journal of Forest Research, 2017)